2004
DOI: 10.1007/s11139-004-0145-1
|View full text |Cite
|
Sign up to set email alerts
|

Bilinear Summation Formulas from Quantum Algebra Representations

Abstract: Abstract. The tensor product of a positive and a negative discrete series representation of the quantum algebra Uq su(1, 1) decomposes as a direct integral over the principal unitary series representations. Discrete terms can appear, and these terms are a finite number of discrete series representations, or one complementary series representation. From the interpretation as overlap coefficients of little q-Jacobi functions and Al-Salam and Chihara polynomials in base q and base q −1 , two closely related bilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 28 publications
(52 reference statements)
1
39
0
Order By: Relevance
“…The Racah coefficients for the tensor product π + k 1 ⊗ π + k 2 ⊗ π − k 3 can now be determined from v m+r n (j; k 1 , k 2 )F r−j m (τ ; k 1 + k 2 + j, k 3 ) = U (j, ρ; k 1 , k 2 , k 3 , τ )F r−n m (ρ; k 2 , k 3 )G r n (τ ; k 1 , ρ, k 2 − k 3 ) dν(ρ; k 1 , k 2 , k 3 , τ ), or equivalently from [29] showed that they occur as spherical functions for SU q (2), see also [31] and [21]. In [33] the Askey-Wilson polynomials occur as matrix elements for representations of U q (su (1, 1)), in [25], [13] and [8] they occur as Clebsch-Gordan coefficients.…”
Section: (84)mentioning
confidence: 99%
“…The Racah coefficients for the tensor product π + k 1 ⊗ π + k 2 ⊗ π − k 3 can now be determined from v m+r n (j; k 1 , k 2 )F r−j m (τ ; k 1 + k 2 + j, k 3 ) = U (j, ρ; k 1 , k 2 , k 3 , τ )F r−n m (ρ; k 2 , k 3 )G r n (τ ; k 1 , ρ, k 2 − k 3 ) dν(ρ; k 1 , k 2 , k 3 , τ ), or equivalently from [29] showed that they occur as spherical functions for SU q (2), see also [31] and [21]. In [33] the Askey-Wilson polynomials occur as matrix elements for representations of U q (su (1, 1)), in [25], [13] and [8] they occur as Clebsch-Gordan coefficients.…”
Section: (84)mentioning
confidence: 99%
“…compatible with the assignmenth A,1 defined by (22) and (25) are introduced for the infinite components of K 1,1 bȳ…”
Section: Infinite Border Stripsmentioning
confidence: 99%
“…. constitute an infinite-dimensional U q sl(2) -moduleV (y) corresponding to the principal unitary series representation π P ρ,0 of U q su(1, 1) with cos θ = 1 2 q 2iρ + q −2iρ [21], [22]. Each representation π P ρ,0 is irreducible [23].…”
Section: The Mixed Casementioning
confidence: 99%
See 1 more Smart Citation
“…for the polynomials (12). We call the polynomials d n (µ(m); a, b|q) dual little q-Jacobi polynomials.…”
Section: Dual Little Q-jacobi Polynomialsmentioning
confidence: 99%